“Greetings from hell (neraka kirim salam)”: a discourse analysis of religious-based cyberbullying of dehijabis - Rosidi, Nur Syifaa; Mohamad Jamil, Siti Nurnadilla (Universiti Sultan Zainal Abidin, 2024)
Many studies have been conducted on cyberbullying discourse in Malaysia, but religious-based cyberbullying discourse has received comparatively less attention. Malaysia’s second place ranking in cyberbullying practices among Asian countries in 2018 is striking, and it is worth highlighting that many public figures in the country have encountered cyberbullying upon deciding to remove their hijab. This paper examines how the first dehijabed Instagram posts by local celebrities, Uqasha Senrose, Emma Maembong and Liyana Jasmay incited religious-based cyberbullying. This paper employs a mixed-methods approach. We examined the initial post-dehijabbing captions, along with a total of 300 comments on these posts. Through a two-tiered coding and categorization process, we identified 168 religious-based comments containingreligious-related terminologies, Arabic expressions, Quranic verses, and Hadith. From this subset, 70 of them exhibit cyberbullying characteristics: Defamation, Defense, Encouragement, Exclusion, Sexual Talk, Insult and Threat/Blackmail. The most prevalent categories, Insult (n=29) and Threat/Blackmail (n=18) were further qualitatively analysed using Laclau and Mouffe’s discourse framework and Halliday’s transitivity analysis. The findings reveal that public figures who have removed their hijab have created a hegemonic intervention that challenges Malay Muslim hegemonic practice. Meanwhile, cyberbullies have created a hegemonic closure to counter the hegemonic intervention created by the dehijabed celebrities through the implementation of “Insult” and “Threat”. Nevertheless, the effects of the hegemonic closure, which involves the stabilization of myths as objective reality and the rearticulation of the transgressors’ identities as the sinners, have reproduced the power imbalance between the dominant group and the antagonists. This paper demonstrated that while such practices allow cyberbullies to reinforce their dominance and hegemonic practices by manipulating religion, it is crucial to problematize religious-based cyberbullying discourse as yet another form of hegemonic intervention that appears to be a natural articulation in contemporary discourse.